Da den danske reformation drog mod vest - Sommer, Mattias Skat (Kirkehistoriske Samlinger, 2017)
Det er alment kendt, at den danske reformation kom sydfra; den unge hertug Christian havde i 1521 hørt og set Martin Luther i Worms, og da han 15 år senere som Kong Christian III gik sejrrigt ud af borgerkrigen, var det Wittenbergteologerne, der blev spurgt til råds om en reformation af kirke, samfund og politik. Kendt er det også, at Danmark-Norge gennem ægteskabspolitik og teologisk interessefællesskab knyttede sig tæt til de ledende lutherske fyrster i kejserriget under reformationskongen og dennes søn, Frederik II. Mens bindingen til Sachsen og svogeren kurfyrst August, der pressede ham politisk til at suspendere Niels Hemmingsen i 1579, til sidst blev for meget for kongen, som resolut afviste Konkordieværket i sine riger, er blevet grundigt undersøgt, mangler der stadig en bedre forståelse af den vestlige politik, som Frederik blev mere og mere tilbøjelig til at følge siden 1570’erne. Sammenfaldende med Frederiks udenrigspolitik var en eksport af dansk reformationsteologi mod vest, som er genstand for undersøgelse i nærværende artikel. Summary As the Danish Reformation went West In the late sixteenth and early seventeenth centuries the writings of Danish theologian Niels Hemmingsen (1513-1600) had a remarkable influence in Protestant, non-Lutheran Western Europe, especially England, Switzerland, and the Low Countries. From 1569, some of his works were printed in, for example, London, Leiden, Antwerp, and even Geneva. At the same time in his native Denmark, the rather Philippist theology that he represented was exchanged in favour of Gnesio-Lutheran views, even if Denmark never adopted the Book of Concord, and both Copenhagen and Saxon printers halted publications of Hemmingsen’s books. The year of 1579, in which Hemmingsen was suspended from his Copenhagen theology chair, constitutes a culmination in Dano-Saxon relations, whereas the fact that he – officially – lost influence in Denmark did not disturb non-Lutheran Protestants’ reception of him. This reception went in tandem with a changing geopolitical context of the Oldenburg dynasty that began to move away from being mainly dependent on Lutheran Germany. Arguing in favour of a ‘long Reformation’ perspective and suggesting that during the reign of Frederik II (1559-1588), Danish policy making began to consider the wider Protestant family and not primarily the Lutheran brethren in the Holy Roman Empire, as it did under Christian III (1534-1559) and the early years after Frederik’s ascension to the Danish-Norwegian throne, the present article examines first the vernacular English Hemmingsen prints from the last decades of the sixteenth century, and then the Remonstrant reception of Hemmingsen in the early seventeenth century. With emphasis on the prefaces to the English Hemmingsen prints, the article categorises these into three different groups, each representing a specific type of reception. Rather than discussing if the prefaces grasped the theology of Hemmingsen or not, their strategies and agendas are put to scrutiny. Around 1610, Hemmingsen was drawn into the formation of Remonstrant theology in the Low Countries. Jacob Arminius (1560-1609) and his followers explicitly referred to Hemmingsen’s theology of divine grace and providence as they launched their criticism of the strict doctrine of predestination that came to characterise mainstream Reformed Christianity of the early modern age. The article briefly discusses the Remonstrant use of Hemmingsen, using it as a point of departure for investigating a dispute in the republic of letters on Hemmingsen’s heritage that was fought between Danish superintendent Hans Poulsen Resen (1561-1638) and Reformed counterparts. During this dispute, when an English theologian published a posthumous work by Hemmingsen that criticised the Gnesio-Lutheran ubiquitarian doctrine, Resen was eventually forced to distance himself from parts of Hemmingsen’s theology. Even though Concordian Lutheranism was not introduced in Denmark, Resen’s theology was reminiscent of the one found in the Book of Concord. As Resen distanced himself from Hemmingsen, he simultaneously began to emphasise Martin Luther and the bonds to Lutheran Germany, especially at the centenary of the Reformation in 1617. Nevertheless, the transportation of Danish Reformation theology to the west also had implications in Denmark, if only indirectly. In the mid-seventeenth century translations of English devotional literaturebecame increasingly popular in Denmark, and Danish students made their perigrinatio academica to Dutch and English universities. Moreover, it seems that it was Resen more than King Christian IV (1588-1648), Frederik II’s son and successor, who embarked on an anti-Hemmingsen course; the king stuck to theological Philippism and engaged in the Thirty Years War with an eye to Pan-Protestantism, while the superintendent’s preferences were much closer to Gnesio-Lutheranism. To put it in a nutshell, the reception of Hemmingsen in Western Europe and its repercussions in Denmark are examples of the creation of a new geopolitical space in the late Danish Reformation. While the Baltic Sea characterises the first phase of the Danish Reformation, with Frederik II and Hemmingsen, the North Sea comes to mark its later phases.